KEBERADAAN KEPEMILIKAN TANAH BERDASARKAN SURAT KETERANGAN TANAH (SKT) DI DESA NAMO GAJAH, KECAMATAN MEDAN TUNTUNGAN, KOTA MEDAN (STUDI KASUS PUTUSAN MA Nomor : 1083 K/ Pdt / 2016) - VIDA RIANITA GINTING (PREMISE LAW JURNAL, 2017)
The case discussed in this thesis is the dispute over the land title in Namo Village, Medan. The decease M. Rasul obtained a piece of land through land buy and sell from Nembai in 1977 pursuant to SKGR in 1984. He passed away and is substituted by his son namely Ahmad. His legal standing is the Letter of Notification of Land in 1978, the Letter of Notification in 1980, and the Notification Deed in 1980 issued by a Notary. Ahmad visited the land location, but apparently it has been possessed by Yopie with legal standing of a Leasehold Certificate in 2006. The Rulingof Medan District Court of appeal pronounce him win as the SKT holder, yet the court of appeal the Level I High Court emphasized Yopie as the Leasehold Certicate holder.